Quantification of metals in surface sediments of the interior bay, Lake Titicaca (Peru) - Moreno Terrazas, Edmundo (2018)
In aquatic ecosystems, sediments are reservoirs of heavy metals when their waters are exposed. The purpose of the study was to quantify metals in surface sediments of the interior bay of Puno, Lake Titicaca, Peru. From january to november 2016 of Cu, Zn, Pb, Cd, As and Hg concentrations were analyzed in the surface sediments of six selected environmental sampling stations by non-probabilistic sampling for convenience. The metals were analyzed by acid digestion where their quantification was by inductively coupled plasma spectrometry with axial view (ICP-AES). When comparing the results with the selected environmental standard, all the elements had concentrations in the recommended ranges, although statistically significant differences existed between the stations (p<0,05). The As and Hg, presented similarities in their values (0,0001 mg.L-1) between the stations. As and Hg, presented similarities in their values between the stations. It was concluded that, the surface sediments of the inner bay of Puno do not present risk due to exposure to total metals, since their concentrations were in the range of allowable values.